Investigation into the compression behaviour of unsaturated damaged Callovo-Oxfordian claystone - Wang Hao; Cui Yu-Jun; Vu Minh-Ngoc; Talandier Jean (E3S Web of Conferences, 2023)
In this study, the compression behaviour of unsaturated damaged COx claystone is investigated by performing high pressure oedometer tests with controlled suction. The damaged oedometer samples were prepared by shearing the claystone in triaxial conditions. Four high pressure oedometer tests were conducted using different controlled suctions. The effects of suction and damage on the swelling and compression were investigated in oedometer. Results show that the intact claystone exhibits a larger swelling strain than that of the damaged one at the same imposed suction. The damaged claystone at a lower suction displays a smaller yield stress and higher compressibility, and exhibits a larger compression index Cc than the intact one, evidencing the effect of damage. In addition, the step compression index Cc* increases with the increase of vertical stress, while deceases with the decrease of suction. This indicates the dependencies of compression behaviour on vertical stress and suction.